Hubungan Terpaan Informasi Rokok Elektrik Lebih Aman 95% dari Rokok Konvensional dan Tingkat Pengetahuan Tentang Rokok Elektrik dengan Minat Menggunakan Rokok Elektrik - Abilangga .; Hedi Pudjo Santosa; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This research is motivated by the use of e-cigarettes in Indonesia. E-cigarettes contain substances that are harmful to the body, but recently there has been information about e-cigarettes being 95% safer than conventional cigarettes and the lack of public knowledge about e-cigarettes. This study aims to determine the relationship between exposure to information that e-cigarettes are 95% safer than conventional cigarettes and the level of knowledge about e-cigarettes and interest in using e-cigarettes. The theory used in this research is the theory of Diffusion of Innovation and the theory of Cognitive Response. The sample in this study found 100 people with an age range of 18 – 39 years who had been exposed to information that e-cigarettes were safer than conventional cigarettes and knew that e-cigarettes were. This sample uses non-probability sampling with a random sampling technique. The results showed that exposure to information on electric cigarettes was 95% safer than conventional cigarettes with an interest in using e-cigarettes had a significance value of 0.004 which exceeded the significance value of 0.01 which means that there is a very significant relationship, the correlation coefficient of 0.234 means that it has a weak and weak relationship strength. So that if the exposure to information about e-cigarettes is 95% safer, then the interest in using e-cigarettes is also high. The results of the research on the level of knowledge about e-cigarettes with interest in using e-cigarettes have a significant value of 0.026 which means a significant relationship, a correlation coefficient of 0.169 means that the strength of the relationship is very weak and positive. So if the level of knowledge about e-cigarettes is high, the interest in using e-cigarettes is also high. Therefore, researchers suggest to multiply clear information about e-cigarettes so that people do not experience confusion and marketers are more aggressive in promoting e-cigarettes so that people are more aware of the presence of e-cigarettes.